(untitled) (Communication & Society, 2016)
This paper examines the most important features of three recent presidential campaigns in Latin America, aiming at knowing the dominant trend in their major pieces of advertising. A comparison is made among the spots of candidates who won the presidential elections held in 2011 in Argentina (Cristina Fernández de Kirchner), 2012 in Mexico (Enrique Peña Nieto) and 2012 in Venezuela (Hugo Chávez), based on the functional theory of political campaign discourse(Benoit, 2003). Through a content analysis of 30 spots -and within them, 139 recording units- the article explores: 1) the type of discursive strategy prevalent in the spots of these winning campaigns, 2) whether topics related to policy aspects prevail or not over those referring to the candidates’ image, and 3) if, in temporal terms, these messages indicate issues from the past or future goals. Two relevant considerations arise from the study. On the one hand, the topic “policy” coexists with the topic “character”; on the other hand, “acclaiming” is more intensely associated with “events of the recent past”, while “attacking” is completely linked to “past events” which belong to previous administrations of those presidents who run for another term in office.